역량기반 교양교과목 운영 방안에 대한 고찰－S대 교과기반 평가(CEA) 사례를 중심으로 - 강상희 (교양교육연구, 14(5), 2020)
21세기 지식기반사회로 진입하면서 등장한 역량기반 교육은 교육의 기능과 역할이 지식이나 정보의전수에서 기존 지식이나 정보를 활용해 새로운 가치를 창출할 수 있는 능력의 배양으로 변화될 필요가있음을 보여주는 시그널이라고 할 수 있다. 본 연구는 역량기반 교양교육이 실질적으로 이루어지기위한 조건이 무엇인가 하는 문제의식에서 출발하였으며, 역량기반 교양교육의 측면에서 교과기반 평가, 즉 CEA 모델의 적용 가능성을 모색하는데 목적이 있다. 역량기반 교육과정은 학습자의 역량 형성을 교육의 핵심가치로 설정하여 교육과정을 설계, 운영하고, 설정된 역량에 근거하여 학생들의 성취정도를 평가하여, 결과를 교육과정 개선에 반영하여 교육의질을 높이려는 시도라고 할 수 있다. 따라서 역량기반 교육과정의 핵심은 교육과정을 구성하고 있는교과목 단위에서 관련 핵심 역량을 학생들이 어느 정도 성취하고 있는지 평가하여 그 결과를 교육과정의운영과 개선에 반영하는데 있다. 역량 기반 교육에 대한 비판도 무시할 수는 없으나 역량기반 교육은실체적 성격을 띠며 중요해지고 있다. 그렇다면 역량 기반 교육의 형식과 내용을 어떻게 채워나갈것인가 하는 방법론이 중요해진다. 본 연구에서는 교과기반 평가를 역량기반 교양교육을 실행할 수 있는 방법론으로 활용할 수 있다고보고, 공학교육인증 프로그램의 CEA 모델을 참고하여 CEA에 기초한 역량기반 교양 교과목 수업운영 모델을 제시하였다. 본 연구는 핵심역량에 기초한 교과목 학습목표 중심의 평가, 즉 CEA에 기초한역량기반 교양교육 운영 사례(practice)를 제시하는 데 의의를 두고 있다. 본 연구는 역량기반 교과목운영에 기초한 개선의 사례로서 미국 공학교육인증 프로그램의 교과목 기반 역량평가 소개, 서울소재S대학에서 2017년 2학기부터 시도한 역량기반 교양 교과목 운영 및 개선 사례를 중심으로 역량 기반교양 교과목 수업설계, 평가방법, 개선안 도출방안에 대한 소개, CEA 적용 교과목 담당 교수의 인식조사결과로 구성되어 있다. 마지막으로 대학마다 상황이 다르므로 대학에 맞는 역량 기반 교양 교과목설계 및 운영 모델을 개발하려는 노력이 필요하다는 전제 하에, CEA에 기초한 역량기반 교양 교육의실행에서 중요한 요소들을 제언하는 것으로 마무리한다. Competency-based education has been emphasized since the turn of the 21st century’s knowledge-based society, in which both technological and industrial innovation have accelerated. Changes in the era and social needs have led to inevitable shifts in the direction and content of education. Competency-based education is a signal that shows that the function and role of education also need to be changed. Despite the criticism that it is being developed as a sort of trendy, educational discourse without sufficient reflection, competency-based education is becoming more and more important, in large part due to its substantive character. As a result, the methodology of how to implement the form and the contents of competency-based education becomes important. The competency-based curriculum is the attempt to set the learner's competency development as the core value of education, design and operate the curriculum, evaluate the achievement level of the students based on the set competency, and to improve the overall quality of education. To be sure, there is no curriculum that does not require some improvement or modification. Improvement is based on evaluation. This is why we need to evaluate the operation of any given curriculum. Competency-based assessments in course units serve as a mechanism for continually improving the curriculum. This is why we have course embedded assessments of competencies in competency-based education. This paper presents a practice for operation and improvement of competency-based liberal arts education based on course embedded assessment. This paper is a kind of case study, which will take into account lecture design, the evaluation method, and the improvement plan (CQI) for the evaluation of competency-based liberal arts courses. The contents of this paper are as follows: First, we introduce conceptual models for the operation and improvement of a competency-based liberal arts curriculum, along with the competency-based courses improvement process based on the ADDIE model. Next, evaluation and improvement cases of competency-based courses are introduced. The case study consists of analyzing and designing the operation of the course, analyzing the results of the evaluation, and deriving the improvement plan for the lecture. Finally, this paper concludes with recommendations. KCI Citation Count: 0